Diagnosis to Detect Porcine Transmissible Gastroenteritis Virus (TGEV) by Optical and Transmission Electron Microscopy Techniques - Martins,A. M. C. R. P. F (Sociedad Chilena de Anatomía, 2013)
The porcine transmissible gastroenteritis is a highly severe contagious disease, caused by virus of the Coronaviridae family, genus Coronavirus. Its epizootic shape can reach a rate of up to 100% mortality in piglets under two weeks of age as a result of severe dehydration. In this study fragments of small intestine and stool samples were collected from 75 autopsied pigs from properties. The samples of the fragments were frozen and sent to the Laboratory of Electron Microscopy, Instituto Biológico, SP, Brazil, for histological and transmission electron microscopic analyses. According to histological H&E technique, atrophy, villous necrosis and destruction of the enterocytes were observed in 35 (46.6%) out of the 75 fragments of the small intestine samples. On the immunohistochemistry technique 19 (25.3%) fragments were positively stained with DAB in the Ag-Ac reaction (MabTGEV). In 19 (25.3%) positive samples analyzed by in situ hybridization, a brown stain of enterocytes was observed, mainly in the epithelial cells of the villi. By the negative staining technique, we visualized enveloped, pleomorphic coronavirus particles, with typical radial projections resembling solar corona, with 140 nm diameter in 21 samples (28%) of the small intestine fragments and in 16 (21.3%) stool samples. In the ultrathin sections of 21 (28%) samples of small intestine, complete coronavirus particles with 80 nm diameter were seen among the microvilli and in the cytoplasm of epithelial cells. Immature particles with 60 nm diameter, budding from cell membrane and from a rough endoplasmic reticulum and also inside the vacuoles were visualized. In 19 (25.3%) out of 75 analyzed samples of small intestine, the antigen-antibody interaction was characterized by aggregation of viral particles in the immunoelectron microscopy technique. In the immunocytochemistry technique, the antigen-antibody interaction was strongly enhanced by the dense colloidal gold particles over the coronavirus in 19 (25.3%) out of the 75 samples of fragments of small intestine examined.